Cleaner gobies can solve a biological market task when the correct cue is larger - Ranucci, Maddalena; Court, Melanie; Pereira, Beatriz P.; Romeo, Daniele; Paula, José Ricardo (Frontiers in Ecology and Evolution, 2024)
Animal cognition is deeply influenced by interactions with the environment. A notable example of sophisticated cognition in the animal kingdom is described by the mutualistic relationship between cleaner fish and clients, where decision-making processes play a pivotal role in partner choice and fish survival. In this context, while extensive research has explored the cognition of the cleaner wrasse Labroides dimidiatus, it is important to note that studies on the cognition of other wrasse species and on its Caribbean counterparts, Elacatinus spp., are limited. Therefore, to extend our comprehension of cognition in cleaner fish with different evolutionary backgrounds, it is important to focus our attention on the genus Elacatinus spp. In this study, we used plexiglass plates as surrogates for clients and assessed the ability of cleaner gobies, Elacatinus oceanops, to solve a biological market task where prioritizing an ephemeral food plate over a permanent one would double the food reward. We varied cue-based decision-making using both ecologically relevant cues (plate, size, and color) and non-relevant ones (presentation side). Additionally, we tested their capacity for reversal learning, an indicator of complex cognitive abilities. Notably, cleaner gobies were able to solve the biological markets task when the distinguishing cue was a larger plate size. Given that these gobies tend to prioritize larger predatory clients in nature, our results align with their natural inclination. Consequently, further research, including studies involving wild individuals, is essential to elucidate the cognitive abilities of the studied species and their implications in the ecological context and evolutionary history.